2012
DOI: 10.1002/cmdc.201100533
|View full text |Cite
|
Sign up to set email alerts
|

The σ‐Hole Phenomenon of Halogen Atoms Forms the Structural Basis of the Strong Inhibitory Potency of C5 Halogen Substituted Glucopyranosyl Nucleosides towards Glycogen Phosphorylase b

Abstract: C5 halogen substituted glucopyranosyl nucleosides (1-(β-D-glucopyranosyl)-5-X-uracil; X=Cl, Br, I) have been discovered as some of the most potent active site inhibitors of glycogen phosphorylase (GP), with respective K(i) values of 1.02, 3.27, and 1.94 μM. The ability of the halogen atom to form intermolecular electrostatic interactions through the σ-hole phenomenon rather than through steric effects alone forms the structural basis of their improved inhibitory potential relative to the unsubstituted 1-(β-D-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 62 publications
0
26
0
4
Order By: Relevance
“…[12,13] In recent years, pyranosyl nucleosides are viewed as important modifications of natural nucleosides, offering promising avenues in the development of novel bioactive agents with promising therapeutic potential. [14][15][16][17][18][19][20][21][22][23][24] In our previous investigations, we demonstrated that base-modified pyranonucleosides rank among the most potent glycogen phosphorylase (GP) [25,26] and thymidylate synthase (TS) [27] inhibitors, and were endowed with a pronounced cytostatic and antiviral action. [28] As a continuation of this research and based on the pharmacological properties of thiopurine analogues, we now report the synthesis and biology of new thiopurine pyranonucleosides via glycosylation of mercaptopurine and thioguanine pyranonucleosides bearing D-glucose, D-galactose, D-xylose, D-mannose, and D-lyxose as sugar moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] In recent years, pyranosyl nucleosides are viewed as important modifications of natural nucleosides, offering promising avenues in the development of novel bioactive agents with promising therapeutic potential. [14][15][16][17][18][19][20][21][22][23][24] In our previous investigations, we demonstrated that base-modified pyranonucleosides rank among the most potent glycogen phosphorylase (GP) [25,26] and thymidylate synthase (TS) [27] inhibitors, and were endowed with a pronounced cytostatic and antiviral action. [28] As a continuation of this research and based on the pharmacological properties of thiopurine analogues, we now report the synthesis and biology of new thiopurine pyranonucleosides via glycosylation of mercaptopurine and thioguanine pyranonucleosides bearing D-glucose, D-galactose, D-xylose, D-mannose, and D-lyxose as sugar moiety.…”
Section: Introductionmentioning
confidence: 99%
“…The 3-(β-D-glucopyranosyl)-5substituted-1,2,4-triazoles studied here are predicted to have drug-like potential with only permeability flagged as a potential issue to efficacy. However, the compounds have in general (for six of the nine synthesized) better predicted Caco-2 cell permeabilities (by a factor of 3)than previously reported glucose analogues[10,55,56] and accordingly are to be considered in further follow up experiments (cellular and in vivo) for efficacy.…”
mentioning
confidence: 78%
“…A large number of synthetic and natural product GP inhibitors targeting the different binding sites have been identified in recent years and solved structures of inhibitor bound GP complexes have facilitated further structure based inhibitor design efforts [4,5,9]. GP inhibitors have demonstrated considerable potential for T2D treatment in cellular models [10][11][12] and in vivo [13][14][15][16], as well as promise against other conditions such as myocardial and cerebral ischemias, and tumors [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…All calculations employed DFT with the M06-2X functional [45] and the all electron MIDIX basis set [46,47] was used for the QM region (the ligands), previously shown to be effective for halogen substituted ligands in studies of this type [48]. The PhKγ-trnc protein was described using MM with the OPLS-AA(2005) forcefield [49].…”
Section: Ic50 Measurementsmentioning
confidence: 99%